ESRA19-0181 Erector spine plane block for laparoscopic gynecologic oncologic surgery: a case series of 10 patients. (30th August 2019) - Frassanito, L; Sonnino, C; Germini, P; Scorzoni, M; Ciancia, M; Giuri, PP; Toni, F; De Martino, S; Olivieri, C; Cantale, A; Settanni, D; Filetici, N; et al.
Abstract : Background and aims: Total laparoscopic hysterectomy (TLH) is associated with significant postoperative pain which worsens outcomes and prolongs hospital stay. 1 The ultrasound guided (UG) erector spinae plane block (ESPB) is a new technique for thoracic analgesia. 2 Few cases have been reported for postoperative analgesia in laparoscopy. 3 We describe the successful use of ESPB to provide postoperative analgesia following THL. Methods: We performed UG bilateral ESPB at T10 level in 10 patients scheduled for TLH after written informed consent. In sitting position, with a linear probe (Sonosite M-Turbo) and in plane cranio-caudal approach, Ropivacaine 0, 5% 20 ml was injected bilaterally. Sensitive block was tested by pinprick. Standard Propofol-Sufentanil-Rocuronium-Sevoflurane general anaesthesia was administered. THL were performed with 12-mm umbilical trocar and 3 accessory 5-mm trocars. A patient control analgesia (PCA) with morphine was delivered. We measured postoperative pain by visual analogue scale (VAS). Results: Four patients underwent TLH, 6 women (60%) had TLH plus salpingo-oophorectomy. Intraoperative median sufentanil was 30 mcg (IQ 30–40). Pinprick was positive bilaterally T4-T10 in 3 patients (30%). VAS scores and Morphine consumption are listed in figure 1 . Conclusions: In literature 24-hour morphine consumption after TLH arise from 10, 6 and 17, 7 mg. 4 ESPB was effective in reducing opioid requirement after TLH. Future research should compare ESPB to other techniques to assess its impact on intraoperative opioid consumption and hospital stay. References: Lirk. Reg Anesth Pain Med . 2019 Apr;44(4):425–436. Forero. Reg Anesth Pain Med . 2016; 41: 621–7. Chin. Anaesthesia . 2017 Apr;72(4):452460. Bacal. J Minim Invasive Gynecol . 2019;26:40–52.